AI Smart Contract: Platform Konversi Poin Program Merdeka Belajar – Kampus Merdeka Berbasis Kecerdasan Buatan - Teguh Trianung Djoko Susanto; Soraya Nuron Jamil; Stevani Reynita; Zaahidah Faadhilah; Winda Dewi Listyasari (Program Studi Manajemen Pendidikan, 2023)
The Merdeka Belajar – Kampus Merdeka (MBKM) policy issued by the Ministry of Education and Culture opens up great opportunities for universities to create graduates who are competent and competitive. The MBKM program gives students the right to take part in learning outside the department or university with the equivalent or conversion of credits. However, the Director General of the Ministry of Education and Culture, Research, Technology and Higher Education, highlighted that there are still many universities that have not provided proper grade conversion rights to students (Kemendikbud, 2022). The Kastrat BEM FMIPA UNEJ team found that 93.7% of students who had taken MBKM were worried because they had to retake credits that had not been converted (Kastrat BEM FMIPA UNEJ, 2022). Through SWOT analysis, this research provides an idea solution in the form of an Artificial Intelligence-based Smart Contract as a value conversion platform for the MBKM program to make it easier for departments to convert student grades according to their needs and core competencies.